Effects of exogenous amylase on the in vitro digestion kinetics of whole-crop maize silages made from flint or dent grain type at different phenological stages grown in tropical condition - Silva, Abias Santos [UNESP]; Ribeiro Pereira, Luiz Gustavo; Pedreira, Marcio dos Santos; Machado, Fernanda Samarini; Campos, Mariana Magalhaes; Cortinhas, Cristina Simoes; Acedo, Tiago Sabella; Santos, Rafael Dantas dos; Pacheco Rodrigues, Joao Paulo; Mauricio, Rogerio Martins; Tomich, Thierry Ribeiro (Wiley-Blackwell, 2020)
The effect of exogenous amylase on the in vitro rumen digestion kinetics of whole-crop maize silage made from dent (RB9004) or flint grain type (RB9308) was evaluated at different phenological stages: soft dough (SOD), early dent (EAD), 1/2 milkline (1/2M) and 3/4 milkline (3/4M). Forage was harvested from 70 to 110 days after sowing. Two rumen-cannulated cows receiving or not exogenous amylase (0.7 g/kg dry matter-DM, provided to achieve 396 kilo Novo units of amylase activity/kg of TMR DM) were used as donor of ruminal fluid. The in vitro gas production kinetics was evaluated according to a dual-pool logistic model. The chemical composition and gas production kinetics were affected by the hybrid and phenological stages. The flint hybrid had lower range for chemical analysis among physiological stages. Harvesting at 1/2M and 3/4M improved DM content, bromatological composition and silage quality parameters compared to dent or flint types. Amylase (i) increased methane (CH4) production and in vitro dry matter digestibility (IVDMD) in 1/2M stage, (ii) improved digestion kinetics by reducing lag time and increasing total gas production and fermentation rates of non-fibrous carbohydrates (NFC) and fibrous carbohydrates (FC), and (iii) increased extent and fermentation rate of NFC and increased fermentation rate of FC fraction in whole-crop maize silages produced from dent or flint types in all phenological stages. Harvesting between 1/2M and 3/4M is the best phenological stage to improve chemical composition and silage quality parameters. Exogenous amylase showed improvements on fibre digestion of silages at 1/2M and 3/4M phenological stages in both grain types of corn.
Keywords: carbohydrates; digestibility; enzyme; harvesting time; methane